2021
DOI: 10.3390/foods10050955
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Processing for the Production of Added-Value Claw Meat from Edible Crab (Cancer pagurus)

Abstract: High-pressure processing (HPP) in a large-scale industrial unit was explored as a means for producing added-value claw meat products from edible crab (Cancer pagurus). Quality attributes were comparatively evaluated on the meat extracted from pressurized (300 MPa/2 min, 300 MPa/4 min, 500 MPa/2 min) or cooked (92 °C/15 min) chelipeds (i.e., the limb bearing the claw), before and after a thermal in-pack pasteurization (F9010 = 10). Satisfactory meat detachment from the shell was achieved due to HPP-induced cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
(125 reference statements)
1
2
0
Order By: Relevance
“…The fresh gonads' physicochemical composition was in accordance with other authors on sea urchins [5,37,38]. The HPP treatments influenced the protein content during the shelf life, leading to lower values than the control samples according to similar trials on fish and crustaceans [39,40]. However, the decrease in the protein fraction was more significant after treatment at 350 MPa than at 500 MPa.…”
Section: Discussionsupporting
confidence: 87%
“…The fresh gonads' physicochemical composition was in accordance with other authors on sea urchins [5,37,38]. The HPP treatments influenced the protein content during the shelf life, leading to lower values than the control samples according to similar trials on fish and crustaceans [39,40]. However, the decrease in the protein fraction was more significant after treatment at 350 MPa than at 500 MPa.…”
Section: Discussionsupporting
confidence: 87%
“…The level of myofibrils in the periopods muscle is higher than that of the muscle in the carapace, and could be processed at high pressure (300 MPa/2 min, 300 MPa/4 min, 500 MPa/2 min) to denature the cold protein of the muscle, which making the shell and meat easier to separate. This method could obtain higher yields and ensure the stability of polyunsaturated fatty acid content, which cannot be achieved by conventional heat treatment [ 27 ].…”
Section: Sustainable Utilization and Problemsmentioning
confidence: 99%
“…After sous-vide cooking, the physicochemical changes induced by HPP did not affect consumer acceptance. Lian et al (2021) found that the appearance of pressure-treated crab claw meat (Callinectes sapidus) turned white. However, it was highly similar to the conventionally cooked-pasteurised claw meat after subsequent thermal pasteurisation.…”
Section: Effects Of Hpp On Aquatic Products Appearancementioning
confidence: 99%